2018
DOI: 10.1177/1747021818776818
|View full text |Cite
|
Sign up to set email alerts
|

Two retrievals from a single cue: A bottleneck persists across episodic and semantic memory

Abstract: There is evidence in the literature that two retrievals from long-term memory cannot occur in parallel. To date, however, that work has explored only the case of two retrievals from newly acquired episodic memory. These studies demonstrated a retrieval bottleneck even after dual-retrieval practice. That retrieval bottleneck may be a global property of long-term memory retrieval, or it may apply only to the case of two retrievals from episodic memory. In the current experiments, we explored whether that apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Importantly, as we already mentioned in the introduction section, participants can flexibly adopt a parallel or serial processing strategy depending on task requirements (Lehle, Steinhauser, & Hübner, 2009;Orscheschek, Strobach, Schubert, & Rickard, 2018;Strobach, Pashler, Schubert, & Rickard, 2014). In line with previous observations of , current research suggests that a parallel strategy is preferred over a serial strategy, even if it leads to higher costs of primary task performance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, as we already mentioned in the introduction section, participants can flexibly adopt a parallel or serial processing strategy depending on task requirements (Lehle, Steinhauser, & Hübner, 2009;Orscheschek, Strobach, Schubert, & Rickard, 2018;Strobach, Pashler, Schubert, & Rickard, 2014). In line with previous observations of , current research suggests that a parallel strategy is preferred over a serial strategy, even if it leads to higher costs of primary task performance.…”
Section: Discussionsupporting
confidence: 84%
“…Despite their differences, both models assume that the presence of a secondary task results in between-task interference and a decrease in performance, which is either due to suspended processing of the second task, or limited resources which need to be shared between both tasks. Interestingly, recent research suggests that participants can process dual-tasks in either a serial (one task at a time) or a parallel (sharing capacity) manner (see Lehle, Steinhauser, & Hübner, 2009;Orscheschek, Strobach, Schubert, & Rickard, 2018;Strobach, Pashler, Control adjustment in dual-tasking Schubert, & Rickard, 2014). However, the underlying conditions of the adopted processing strategy remain unclear.…”
Section: Control Adjustment In Dual-taskingmentioning
confidence: 99%
“…Because response chunking is an associative memory process that would occur during a dual-retrieval trial, this response chunking account suggests that learned retrieval parallelism occurs at the individual cue-response level (i.e., for old cues only) rather than at the task level (i.e., for old and new cues). Consistent with that possibility, Orscheschek et al (2019) and Strobach, Schubert, et al (2014) have shown that this parallelism did not transfer to cues for which only single-retrieval practice occurred during the practice phase, with dual-retrieval trials introduced only during a transfer phase. In this way, empirical evidence in dual tasks with two long-term memory retrieval tasks showed the existence of the DTPA phenomenon and provided evidence that is consistent with the integration hypothesis (i.e., the chunking mechanism; Nino & Rickard, 2003).…”
Section: Practice Mechanismsmentioning
confidence: 80%
“…The findings of the dual-retrieval practice studies (Orscheschek et al, 2019;Strobach, Schubert, et al, 2014) are incompatible with assumptions of the allocation and scheduling hypothesis since there is no evidence for transfer of learned retrieval parallelism between old and new cues within the same blocks of dual-memory retrieval (i.e., old and new cues were presented under very similar conditions). Alternatively, the literature on dual tasks with two long-term memory tasks discusses one variation of the integration hypothesis.…”
Section: Practice Mechanismsmentioning
confidence: 96%
See 1 more Smart Citation